A rationally designed perfluorinated host for the extraction of PFOA from water utilising non-covalent interactions. (23rd November 2017) - Omorodion, Harrison; Palenzuela, Miguel; Ruether, Manuel; Twamley, Brendan; Platts, James A.; Baker, Robert J.
Abstract : Three hosts for the encapsulation of perfluorooctanoic acid have been synthesized. The host:guest complexes have been characterized by multinuclear NMR spectroscopy in solution and the solid state. Abstract : Perfluorooctanoic acid (PFOA) is a persistent organic pollutant and widespread in the environment. Three hosts have been synthesized based upon the formation of a fluorous cavity and hydrogen bonding receptors with the aim of extracting PFOA from water into organic solvents. The hosts based upon a calix[4]arene functionalized at the lower rim with amide groups and fluorous ponytails are effective for the quantitative removal of PFOA. Modification to a partial cone or a trisaminoamine framework reduces the conformational rigidity and lowers the extraction efficiency. A comprehensive NMR spectroscopic analysis both in solution and the solid state, along with other characterization techniques, has elucidated the stoichiometry of the host:guest species and the binding constants have been measured. A computational study has given further insight into the binding modes and corroborated the spectroscopic measurements.